Grain refinement of LM25 Aluminum alloy casting using sloping plate process - Qayyum, J.A. (Asian Research Publishing Network, 2016)
Grain refinement during semi-solid processing is believed to augment the mechanical properties of metals. The introduction of nucleation in the die pool, generated as a result of localize solidification of molten metal, over a sloping plate can serve as an economical and efficient way for grain refinement. In this research, flow from the sloping plate was used for enhancement of material properties through grain refinement in gravity die casting using Aluminum alloy LM25. The castings were prepared with different slope angles of 800mm long, naturally cooled Stainless Steel plate, with varying angles of 150 increments with the horizontal. The specimens obtained were then tested for microstructure characterization, tensile strength and percentage elongation. Conclusions were drawn on the grain size and precipitate morphology as a function of angle of sloping plate. Microstructure examination, elongation measurements and tensile tests show that best properties were achieved with the sloping angle of 60Â°. Â© 2006-2016 Asian Research Publishing Network (ARPN).